Childcare and parenting practices in Singapore: A comparison of fathers' and mothers' involvement. (5th December 2014) - Shan, Cheung Hoi; Hawkins, Russell
Abstract : The extent to which fathers and mothers adopted various childcare and parenting practices in Singapore was examined. Interviews were conducted with 530 parent–child dyads (involving 1060 participants), with parents and children (from age 10–12) responding independently and concurrently in separate rooms. Mothers were more likely than fathers to be children's main and preferred caregivers. Fathers reported using less physical punishment than mothers did, and were also perceived to be less warm and accepting by their children. These findings support the view that power assertive discipline may still be compatible with warmth in parenting at least in this culture. In Confucian societies, parenting concepts involving elements of authoritarianism may be seen as a positive sign of concern.